2018
DOI: 10.1016/j.scitotenv.2018.03.369
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of endocrine disruptors effects on zebrafish (Danio rerio) embryos by untargeted LC-HRMS metabolomic analysis

Abstract: Bisphenol A (BPA), perfluorooctane sulfonate (PFOS), and tributyltin (TBT) are emerging endocrine disruptors (EDCs) with still poorly defined mechanisms of toxicity and metabolic effects in aquatic organisms. We used an untargeted liquid chromatography-high resolution mass spectrometry (LC-HRMS) metabolomic approach to study the effects of sub-lethal doses of these three EDCs on the metabolic profiles of zebrafish embryos exposed from 48 to 120hpf (hours post fertilization). Advanced chemometric data analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 52 publications
7
71
0
Order By: Relevance
“…Cases of mortality may be due to the soft extraction of polyethylene microbeads using 1% DMSO that may have induced leaching of toxic additives and Endocrine-Disrupting Chemicals (EDCs). In accordance with literature outside of this study, these leached chemicals may have disrupted metabolic pathways [5,85], alter gene integrity [85,86], and cause cell apoptosis [87]; hence possibly resulting in Danio rerio toxicity during embryogenesis; however, this needs a more thorough study at gene level. Adherence of polyethylene microbeads to the chorionic membrane may also have disrupted gas exchange and induced hypoxia [5].…”
Section: Conclusion and Recommendationssupporting
confidence: 84%
See 2 more Smart Citations
“…Cases of mortality may be due to the soft extraction of polyethylene microbeads using 1% DMSO that may have induced leaching of toxic additives and Endocrine-Disrupting Chemicals (EDCs). In accordance with literature outside of this study, these leached chemicals may have disrupted metabolic pathways [5,85], alter gene integrity [85,86], and cause cell apoptosis [87]; hence possibly resulting in Danio rerio toxicity during embryogenesis; however, this needs a more thorough study at gene level. Adherence of polyethylene microbeads to the chorionic membrane may also have disrupted gas exchange and induced hypoxia [5].…”
Section: Conclusion and Recommendationssupporting
confidence: 84%
“…Incidences of embryos exhibiting lack of somite formation and non-detachment of tail were observed in Danio rerio treated with PE-MBS (S2 Appendix) and may be attributed to chemical additives and EDCs added to pre-production polyethene microplastics [85]. Related literature outside of this study suggests that observed toxic endpoints related to somite defect may be associated with ectodermal implications during somitogenesis [91].…”
Section: Embryotoxicitymentioning
confidence: 64%
See 1 more Smart Citation
“…The presence of BPA in the midstream samples (BM, FM, SM and TM) of the rivers might result from a combination of waste dump, especially improperly disposed plastic packagings and runoff. Sub-lethal doses of bisphenol A in the aquatic environment have been shown to have adverse effects on the developing zebrafish embryos (Ortiz-Villanueva et al 2018). BPA has been implicated in infertility, obesity, cancer and neurologic impairments (Saal et al 2012;Itoh et al 2012 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It may remain in the soil up to 4 years and might be washed to rivers or leached to groundwater where it degrades slowly (U.S. Environmental Protection Agency 2007). There are various reports of the effects of EDCs on wildlife, especially in freshwater ecosystems, such as abnormal development and death of embryos (Arukwe et al 2016;Ortiz-Villanueva et al 2018), changes in sexual behaviour (Kanda 2019), feminization of male animals (Carnevali et al 2018) and altered immune functions (Nowak et al 2019). The effects of EDCs had also been recorded in birds, especially those feeding in polluted waters (Roman et al 2019;Jessl et al 2018) and may ultimately lead to loss of biodiversity.…”
Section: Introductionmentioning
confidence: 99%